Regulatory roles of insulin growth factor binding protein family in neuroblastoma cell proliferation and differentiation: Potential prognostic biomarkers and therapeutic targets for neuroblastoma - Kai Huang; LinYu Yang; Yue Ma; Shan Wang (Wiley, 2024)
Abstract Neuroblastoma (NB), as a representative of tumors of embryonic origin in children, has specific clinical features. On the one hand, a very small number of NBs may appear to regress on their own. On the other hand, highly malignant NBs can invade the surrounding blood vessels and organs and metastasize to distant bone, bone marrow, and lymph nodes in the early stages of the disease. Based on differential affinities to insulin growth factors (IGFs), insulin growth factor binding proteins (IGFBPs) are classified into two groups: IGF binding proteins (IGFBP1‐6) with high‐affinity and IGF low‐affinity binding proteins, such as IGFBP‐related proteins (IGFBP rP1‐10). IGFBP are crucial regulators of the bioavailability and function of IGF in metabolic signaling and as modulators of IGF signaling, and their role in NB is gaining increasing attention. In this study, we investigate the involvement of IGFBP family members in the growth and differentiation of NB cells, as well as the potential of IGFBPs as prognostic biomarkers and therapeutic targets for human NB.